2021
DOI: 10.1038/s41598-021-02262-7
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoplasmonic immunosensor for the detection of SCG2, a candidate serum biomarker for the early diagnosis of neurodevelopmental disorder

Abstract: The neural circuits of the infant brain are rapidly established near 6 months of age, but neurodevelopmental disorders can be diagnosed only at the age of 2–3 years using existing diagnostic methods. Early diagnosis is very important to alleviate life-long disability in patients through appropriate early intervention, and it is imperative to develop new diagnostic methods for early detection of neurodevelopmental disorders. We examined the serum level of secretogranin II (SCG2) in pediatric patients to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…TargetScan analysis revealed that SCG2 is a direct target of miR-155, which was downregulated in nitrate-exposed SH-SY5Y cells. Earlier research has indicated that SCG2 overexpression in plasma is a biomarker for early neurodevelopmental disorders [45]. SLU7, regulates the process of alternate splicing [46].…”
Section: Discussionmentioning
confidence: 99%
“…TargetScan analysis revealed that SCG2 is a direct target of miR-155, which was downregulated in nitrate-exposed SH-SY5Y cells. Earlier research has indicated that SCG2 overexpression in plasma is a biomarker for early neurodevelopmental disorders [45]. SLU7, regulates the process of alternate splicing [46].…”
Section: Discussionmentioning
confidence: 99%